Decision-making in agricultural sector in view of the environment - Chunmei Ji (КНУБА, 2019)
The article deals with the main approaches to decision-making in the agrarian sector. The conceptual basis of decision-making is conducted. The peculiarities of national approaches to decision making are considered. The questions of management and peculiarities of its application in agrarian sphere are considered. The approach-analysis-assessment-diagnosis as a basic stage for further research is considered. Peculiarities of monitoring of objects of agrarian sphere are considered. The use of statistical methods of analysis and forecasting, in particular, multidimensional statistical methods during economic monitoring, is substantiated. The ability to determine the relationship between environmental and economic indicators by means of statistical methods is shown. The mutual influence of agriculture and ecological factors is considered, which determines the necessity of making decisions on increase of efficiency of use of natural resources and application of new approaches to agriculture.
Keywords: agriculture; decision-making; ecology; 005.53:63]:504